Źabs-dkar Tshogs-drug-raṅ-grol gyi bkaʼʼ bum = The collected works of Źabs-dkar Tshogs-drug-raṅ-grol - Źabs-dkar Tshogs-drug-raṅ-grol, 1781-1851 (Lama Ngodrub and Sherab Drimey, 1980)
Collected works of a Tibetan Buddhist who advocated a combination of Nyingmapa and Gelukpa practices.